Proceedings of the International Dental Conference of Sumatera Utara 2017 (IDCSU 2017) 2018
DOI: 10.2991/idcsu-17.2018.72
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal and Genetic Role Affecting the Bone Resorption in Patients with Osteoporosis

Abstract: Abstract-Increasing age, especially in postmenopausal women, shows a decline in anabolic hormones activity and an increase in anti-anabolic hormones activity. This causes bone resorption and may lead to osteoporosis. Osteoporosis is a degenerative disorder marked by decrease in bone mass because of imbalance between bone resorption and formation. Bone strength is determined by morphology, bone structure & geometry, bone remodelling and quality of extracellular matrix. The balance in bone resorption and formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Psychological coping against COVID-19 aims to prevent prolonged psychological stress during COVID-19. The level of anxiety in adolescents is also influenced by the increasing level of maturity of a person towards the problems or threats they face and the increasing ability or perspective of a person in dealing with life experiences as they get older (Puspitadewi & Auerkari, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Psychological coping against COVID-19 aims to prevent prolonged psychological stress during COVID-19. The level of anxiety in adolescents is also influenced by the increasing level of maturity of a person towards the problems or threats they face and the increasing ability or perspective of a person in dealing with life experiences as they get older (Puspitadewi & Auerkari, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Status: Another study showed that the duration of menopause, as well as the age and duration of diabetes, were amongst risk factors for decreasing BMD in diabetic postmenopausal women. It is obviously known that osteoporosis is a problem related to age and hormonal changes in women, suggesting a hormonal influence on BMD 12 . Moreover, similar findings were reported in postmenopausal women with T2DM using QUS 13 .…”
Section: Socio-demographic Data and Bone Healthmentioning
confidence: 99%